Anthropometric Measures and the Risk of Coronary Artery Disease - Aidin Baghbani-Oskouei; Mehrzad Gholampourdehaki (Babol University of Medical Sciences, 2020)
Background: Nowadays, obesity and overweight are projected to become main risk factors for coronary artery disease (CAD). We aimed to determine the association of anthropometric measures with presence of significant (sig.) CAD as evaluated by coronary angiography, among an adult Iranian population. Methods: The present study included 441 patients (men=275) aged > 30 years with suspected CAD, who had undergone coronary angiography between January 2019 and November 2019. All demographic data and patients' medical history as well as clinical examinations were recorded by a trained physician. Coronary angiography was performed using standard techniques to determine the presence of sig. coronary artery lesions. Logistic regression analyses were conducted to assess the odds ratio (OR) of each anthropometric measure for the presence of sig. CAD. Results: The mean age of participants was 51.2±8.7 years and sig. CAD was detected in 185 patients. Univariate analyses showed that body mass index (BMI), waist circumference (WC), and waist to hip ratio (WHR) were significantly associated with increased risk of CAD. On multivariable logistic regression model, BMI and WHR correlated independently with increased risk of CAD; while higher WC and wrist circumference (WrC) could not predict the CAD risk. The corresponding ORs (95% confidence interval) were 1.36 (1.04-1.74), 1.17 (0.95-1.63), 1.29 (1.12-1.41), and 1.24 (0.76-1.92) for BMI, WC, WHR, and WrC, respectively. Considering the receiver operating characteristic analysis, no superiority was observed for each of the measures for discriminating sig. CAD from non-sig. CAD status. Conclusion: BMI and WHR are independently associated with the presence of CAD among Iranian population. These results emphasize the value of anthropometric assessment among those with suspected CAD.